An immunofluorescence study on VEGF and extracellular matrix proteins in human periodontal ligament during tooth movement. Issue 10 (October 2019) - Militi, Angela; Cutroneo, Giuseppina; Favaloro, Angelo; Matarese, Giovanni; Di Mauro, Debora; Lauritano, Floriana; Centofanti, Antonio; Cervino, Gabriele; Nicita, Fabiana; Bramanti, Alessia; Rizzo, Giuseppina
Abstract: The periodontal ligament (PDL) is a highly vascularized connective tissue surrounding the root of a tooth. In particular, the PDL is continuously exposed to mechanical stresses during the phases of mastication, and it provides physical, sensory, and trophic functions. It is known that the application of orthodontic force creates a change in periodontal structures. In fact, these forces generate a pressure on the ligament that closes the vessels. The aim of this study is to observe the modifications of vascular endothelial growth factor (VEGF) in the PDL and extracellular matrix proteins after application of a pre-calibrated and constant orthodontic force at different phases of treatment. We used a 50-g NiTi coiled spring and in vivo samples of PDL of maxillary and mandibular premolars of patients subjected to orthodontic treatment. These teeth were extracted at 1, 7, 14, 21, and 30 days, respectively, by application of force. The extraction of the PDL was effectuated by scarifying the radicular surface on the pressure and tension sides. The mechanical stress induced by the application of force caused an increase in the reactive type of metabolism of extracellular matrix proteins and modulation of neoangiogenesis until restoration.